Solve by the addition method. (You may first have to multiply both sides of one equation by -1) Problem: 3x+y=13 x+y=3

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

so would I do it like this: x+ (-1) y=3(-1) ? then solve

you need x to times -1 too, like this (-1)(x+y)=3(-1)
(-1)x + (-1)y = 3(-1)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.